Dysfunction of the prefrontal cortex in addiction: neuroimaging findings and clinical implications - Goldstein, Rita Z.; Volkow, Nora D. (Nature reviews. Neuroscience, 2011)
Key Points Neuroimaging studies have revealed an emerging pattern of generalized prefrontal cortex (PFC) dysfunction in drug-addicted individuals that is associated with worse outcome — more drug use, worse PFC-related task performance and greater likelihood of relapse. Widespread PFC activation in drug-addicted individuals upon taking cocaine or other drugs and upon presentation of drug-related cues is replaced by widespread PFC hypoactivity during exposure to higher-order emotional and cognitive challenges and/or during protracted withdrawal when not stimulated. The nature of the findings in PFC is different when abusers are studied during intoxication or craving and when they are studied during acute or protracted withdrawal, and this is to be expected considering the distinct role of the PFC in these processes. PFC regions may be implicated in what seem to be opposite processes. This may reflect the limited temporal resolution of imaging technologies or methodological variability. Processes also reflect the function of networks rather than isolated regions, so that the output of a region will differ as it connects with different networks. Although activity among PFC regions is highly integrated and flexible, such that any one region is involved in multiple functions, the dorsal PFC (including the dorsal anterior cingulate cortex, dorsolateral PFC and inferior frontal gyrus) has been predominantly implicated in top-down control and meta-cognitive functions (including awareness), the ventromedial PFC (including subgenual ACC and medial orbitofrontal cortex) in emotion regulation (including conditioning and assigning incentive salience to drugs and drug-related cues), and the ventrolateral PFC and lateral OFC in automatic response tendencies (for example, drug-related attention bias) and impulsivity. Dysfunction of these PFC regions may contribute to impaired response inhibition and salience attribution (iRISA) in addiction, neuropsychological mechanisms that underlie the development of craving, compulsive use and impaired self-awareness (previously labelled 'denial' of illness and/or need for treatment), which are characteristic symptoms of drug addiction. PFC dysfunction may in some instances precede drug use and confer vulnerability for (or protection against) developing substance use disorders. Specific biomarkers could be targeted for intervention purposes. For example, PFC abnormalities could be used to identify the children and adolescents who would benefit most from intensive drug abuse prevention efforts. The combination of targeted pharmacological interventions (for example, to enhance dopaminergic neurotransmission) with cognitive–behavioural exercises (for example, to enhance inhibitory control and non drug-related motivation, and reduce drug-related attention bias) could normalize select PFC functions. Ameliorating these deficits could help addicted subjects to engage in rehabilitation treatment. Functional imaging studies have pointed to a key role for the prefrontal cortex (PFC) in addiction, both through its regulation of limbic regions and its involvement in higher-order executive function. Goldstein and Volkow review these studies, showing that disruption of the PFC in addiction not only underlies compulsive drug taking but also accounts for the disadvantageous behaviours that are associated with addiction and the erosion of non-drug related motivation and self-control. The loss of control over drug intake that occurs in addiction was initially believed to result from disruption of subcortical reward circuits. However, imaging studies in addictive behaviours have identified a key involvement of the prefrontal cortex (PFC) both through its regulation of limbic reward regions and its involvement in higher-order executive function (for example, self-control, salience attribution and awareness). This Review focuses on functional neuroimaging studies conducted in the past decade that have expanded our understanding of the involvement of the PFC in drug addiction. Disruption of the PFC in addiction underlies not only compulsive drug taking but also accounts for the disadvantageous behaviours that are associated with addiction and the erosion of free will.